Infusion rate and pharmacokinetics of intravenous pamidronate in the treatment of tumour-induced hypercalcaemia. Issue 800 (June 1992) - Dodwell, D. J.; Howell, A.; Morton, A. R.; Daley-Yates, P. T.; Hoggarth, C. R.
Abstract : We report the results of two consecutive randomized studies in the treatment of malignant hypercalcaemia with intravenous pamidronate. Overall normocalcaemia was achieved in greater than 90% of patients and a single infusion of 60 mg pamidronate given over 2 hours was as effective in restoring normocalcaemia as infusions given over 4, 8 or 24 hours. Similarly duration of normocalcemia after treatment with pamidronate and the control of the symptoms of hypercalcaemia were independent of infusion rate. Study of the pharmacokinetics of pamidronate in the treatment of hypercalcaemia show this drug to have a very high clearance due to calcified tissue retention and renal excretion. The initial half life of the drug in plasma is very short and most of the drug is cleared before distribution equilibrium is achieved. Short infusions of pamidronate are as safe and effective as infusions given over a longer time and are therefore to be preferred because of their greater convenience.